Barrington Atlas of the Greek and Roman World, ed. Richard J. A. Talbert - Petrović, Vladimir P. (Balcanica - Annual of the Institute for Balkan Studies, 2023)
Barrington Atlas of the Greek and Roman World, ed. Richard J. A. Talbert, Princeton, 2000.